Framework Media di Dunia - Munadhil Abdul Muqsith (UIN Syarif Hidayatullah Jakarta, 2021)
The intellectual struggle that is presented in various print and electronic mass media is the impact of the freedom to obtain and disseminate information. The mass media that used to be only in the form of print media has now turned into online media which makes it easier for anyone to access it. No wonder most people say that technology has become the prima donna for modern human civilization in the 21st century. Keywords: Framework; Media; Technology